LOCAL WISDOM IN UTILIZING PEAT SWAMP SOIL AND WATER TO IMPROVE QUALITY OF GELAM WOOD - Supriyati, Wahyu; Alpian, Alpian; Prayitno, T. A.; Sumardi, Sumardi; Marsoem, Sri Nugroho (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Local wisdom in utilizing swamp soil and water to improve the quality of gelam wood in Central Kalimantan becomes an interesting phenomenon. Improving the quality of wood can economize on the use of wood, which in turn preserves the forests in peat swamp lands. Gelam (Melaleuca sp.) woods that are mostly found in peat swamp forests can be used as piles/stakes in swamp soil, and they are durable for decades. The general objective of this study was to provide a scientific explanation of the effect of peat swamp soil and water on improving the quality of gelam wood either in barked and barkless conditions. This study was conducted by taking gelam trees that grew in Central Kalimantan. It was carried out for 18 months, and investigated the barked/barkless woods, media (swamp water, freshwater, peat swamp soil, and sandy soil) and 3 lengths of burying times. Wood properties analyzed were physical and mechanical properties. The standard of physical-mechanical property tests referred to British Standard 373.The results showed that the interaction between bark factor (A) and media (B) affected specific gravity. Barked wood produced the highest spesific gravity in swamp water medium. Water media (swamp and fresh water) improved the wood’s specific gravity more than soil media (swamp and sandy soil). The highest values of hardness, stress on Proportional Limit, and Modulus of Elasticity were in the medium of swamp soil. The improvement of the quality of gelam woods, which were either buried or used as stakes/piles, was allegedly resulted from the swamp water infiltrating into gelam woods that thereby increased the specific gravity.